Latin American Initiative for Lifestyle Intervention to Prevent Cognitive Decline (LatAm‐FINGERS): Study design and harmonization - Crivelli, Lucía (2023)
INTRODUCTION: Latin American Initiative for Lifestyle Intervention to Prevent Cognitive Decline (LatAm-FINGERS) is the first non-pharmacological multicenter randomized clinical trial (RCT) to prevent cognitive impairment in Latin America (LA). Our aim is to present the study design and discuss the strategies used for multicultural harmonization. METHODS: This 1-year RCT (working on a 1-year extension) investigates the feasibility of a multi-domain lifestyle intervention in LA and the efficacy of the intervention, primarily on cognitive function. An external harmonization process was carried out to follow the FINGER model, and an internal harmonization was performed to ensure this study was feasible and comparable across the 12 participating LA countries. RESULTS: Currently, 1549 participants have been screened, and 815 randomized. Participants are ethnically diverse (56% are Nestizo) and have high cardiovascular risk (39% have metabolic syndrome). DISCUSSION: LatAm-FINGERS overcame a significant challenge to combine the region´s diversity into a multi-domain risk reduction intervention feasible across LA while preserving the original FINGER design.